GAMBARAN PENGGUNAAN PPI DAN H2RA PADA PASIEN DISPEPSIA DI INSTALASI GAWAT DARURAT RUMAH SAKIT UMUM NEGARA - I Gede Bagus Indra, Marangyana; Ella, Yunita (Institut Teknologi dan Kesehatan Bintang Persada, 2023)
Dyspepsia is a syndrome consisting of pain or discomfort in the pit of the stomach, bloating, nausea, vomiting, belching, feeling full quickly, and feeling full. This disease is one type of disease with a high prevalence in Indonesia and in the world. This study aims to determine the profile and description of the use of PPI and H2RA in dyspeptic patients at the Emergency Unit in Negara General Hospital on January - December 2021. This study was a non-experimental descriptive study with retrospective data collection method. The results of the study showed that the most patients were female by 56% (132 people), age group > 55 years by 27.35% (64 people), private employee occupation by 39.32% (92 people) and the last education was Senior High School by 38.46% (90 people). The most frequently prescribed drugs for dyspeptic patients were oral PPI + H2RA injection by 32.05% (75 people).